Nursing management of upper gastrointestinal bleeding in an elderly patient with gastric carcinoma (1例高龄胃癌患者上消化道出血的护理) - CHEN Qiannan (陈倩楠); DING Jiao (丁姣); QIAN Zhigang (钱志刚) (中西医结合护理)
This paper reported the nursing experience of an 80-year-old patient with gastric cancer complicated with up gastrointestinal bleeding. The patient was critically ill and required multiple life support and multidisciplinary cooperation. Key nursing issues included the establishment and nursing of venous access, observation and nursing of digestive tract bleeding; dynamic monitoring of nutritional status and prevention of pressure ulcers, psychological nursing. (本文报告1例80岁胃癌患者并发消化道出血的护理经验。患者病情危重, 需多种生命支持与多学科合作。护理重点包括静脉通路的建立与护理, 消化道出血的病情观察与护理, 动态监测患者营养状况, 预防压疮, 重视心理护理等。)